Alleviating gender dysphoria: A qualitative study of perspectives of trans and gender diverse people. Issue 1 (January 2022) - Kerr, Lucille; Jones, Tiffany; Fisher, Christopher M
Objectives: This study sought to explore perspectives of trans and gender diverse (TGD) people of ways to alleviate gender dysphoria in service provision and to develop a framework for application in health and other areas that can be used by researchers and service providers to design study protocols, assess organisations and enhance everyday practice in ways that are sensitive to TGD people's experiences. Methods: Data from a national Australian survey on TGD people conducted in 2018–2019 (n = 340) were used to develop a framework for alleviating dysphoria. Participants were asked an open-ended question on ways that body discomfort could be minimised in clinical encounters. Inductive thematic analysis was used to develop themes true to participant sentiment, which formed the basis for the development of a framework. Results: The sample was overall young, with 60.6% aged 18–24, and a strong representation of gender diverse people (42.6%). The most important theme for participants was the context of the experience, which included the subthemes of the interpersonal qualities of service providers, language and pronouns, and practical aspects. Aspects of systems were also important, with education and awareness being particularly emphasised, followed by inclusive environments. Access to gender affirming medical and surgical procedures was rarely mentioned (2.6%). A minority of participants indicated that there was nothing that could be done to alleviate their gender dysphoria (4.4%). Conclusions: The study proposes a framework that can help facilitate assessment of a service's current practices, inform a practitioner's daily practice and be used by researchers to appropriately design studies. The most important areas to address centre on the context of the immediate experience, which may be influenced through systems-level characteristics.